2021
DOI: 10.1080/1528008x.2021.1964413
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Intelligence Profile of Tourists and Its Impact on Tourism

Abstract: The study aims to characterize, for the first time, the emotional intelligence profile of the tourists visiting the city of Porto as well as to observe its influence on the intention to return and activities perfomed during the stay, along with other sociodemographic factors,To achieve these purposes, we used a sample of 886 responses with the following purposes: on the one hand, to get the emotional intelligence constructs by applying the confirmatory factorial analysis, and on the other hand, to apply a logi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 90 publications
(155 reference statements)
2
10
0
Order By: Relevance
“…Finally, the FQFD analysis of this study revealed that brand attachment has a significant influence on the choice of brand experience strategy management plans, both in the data sets analyzed and in different groups (young and older consumers) [69]. In other words, when consumers experience a brand, it evokes positive and multiple psychological attachments and has a favorable impact on the emotional bond between consumers and the brand [70]. This confirms the findings of Japutra et al's [71] exploratory study, which found that young consumers in the UK showed attachment to Fatface Clothing because of their enjoyment of the service experience offered by the retailer.…”
Section: Discussion Of Resultsmentioning
confidence: 72%
“…Finally, the FQFD analysis of this study revealed that brand attachment has a significant influence on the choice of brand experience strategy management plans, both in the data sets analyzed and in different groups (young and older consumers) [69]. In other words, when consumers experience a brand, it evokes positive and multiple psychological attachments and has a favorable impact on the emotional bond between consumers and the brand [70]. This confirms the findings of Japutra et al's [71] exploratory study, which found that young consumers in the UK showed attachment to Fatface Clothing because of their enjoyment of the service experience offered by the retailer.…”
Section: Discussion Of Resultsmentioning
confidence: 72%
“…Notably, such a result may appear because the questionnaire was completed while the respondents were conscious of other people's grooming behaviour. In this vein, the study outcome is partially associated with Borgers et al's [56] finding that assessment of others' emotions makes tourists' decision to return to the destination.…”
Section: Discussion Of Resultsmentioning
confidence: 94%
“…This method that relying on smart services can improve tourists' sense of happiness during trips [56]. Similarly, there is a guiding relationship between tourists' emotional intelligence and travel intention [57]. Based on the experience of related research, this research focuses on tourists' perception and willingness, with this method being used to help obtain accurate data from tourists' questionnaire.…”
Section: Methodsmentioning
confidence: 99%